Simultaneous Roll Transfer and Interconnection of Flexible Silicon NAND Flash Memory. Issue 38 (20th July 2016) - Kim, Do Hyun; Yoo, Hyeon Gyun; Hong, Sung Min; Jang, Bongkyun; Park, Dae Yong; Joe, Daniel J.; Kim, Jae‐Hyun; Lee, Keon Jae
Abstract : Ultrathin silicon‐based flexible 16 × 16 NAND flash memory (f‐NAND) is demonstrated utilizing roll‐to‐plate packaging. The roll‐based thermo‐compression bonding of the anisotropic conductive film (ACF) transfers and simultaneously interconnects the f‐NAND on a flexible printed circuit board. Reliable circuitry operation of the 16 × 16 f‐NAND is confirmed with excellent flexibility and stable ACF interconnections.